2016
DOI: 10.1016/j.amepre.2015.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Toking, Vaping, and Eating for Health or Fun

Abstract: Combusted modes of marijuana use are most prevalent among U.S. adults, with a majority using marijuana for recreation. In light of changing policies and patterns of use, improved marijuana surveillance is critical for public health planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
163
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 304 publications
(174 citation statements)
references
References 29 publications
11
163
0
Order By: Relevance
“…This is a time of significant technological innovation and commercialization regarding alternative modes of marijuana consumption, particularly in places like Colorado that have legalized marijuana (Budney et al, 2015;Debertin, 2014;MacCoun & Mello, 2015;Schauer et al, 2016;Schroyer, 2015;Walsh, 2013;Weiss, 2015). Specifically, vaporizers and edibles have increased in terms of their sales and their prominence in popular culture (Hopfer, 2014;MacCoun & Mello, 2015;Malouff et al, 2014;Schroyer, 2015).…”
Section: Alternative Modes Of Marijuana Consumptionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a time of significant technological innovation and commercialization regarding alternative modes of marijuana consumption, particularly in places like Colorado that have legalized marijuana (Budney et al, 2015;Debertin, 2014;MacCoun & Mello, 2015;Schauer et al, 2016;Schroyer, 2015;Walsh, 2013;Weiss, 2015). Specifically, vaporizers and edibles have increased in terms of their sales and their prominence in popular culture (Hopfer, 2014;MacCoun & Mello, 2015;Malouff et al, 2014;Schroyer, 2015).…”
Section: Alternative Modes Of Marijuana Consumptionmentioning
confidence: 99%
“…Specifically, vaporizers and edibles have increased in terms of their sales and their prominence in popular culture (Hopfer, 2014;MacCoun & Mello, 2015;Malouff et al, 2014;Schroyer, 2015). Vaporizers are electronic devices that heat plant matter or marijuanabased oil and release a mist that is then inhaled (Budney et al, 2015;Malouff et al, 2014;Schauer et al, 2016). There has been a recent and substantial proliferation of companies selling different types of vaporizers (Schroyer, 2015).…”
Section: Alternative Modes Of Marijuana Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Schauer et al, 7.6 % of current marijuana users in a US adult general population survey reported using 'vaporisers' (whether ENDS or specific cannabis vaporisers) to take marijuana [20]; this translates to approximately 0.5 % of the total population surveyed which is much lower than the reported use in the population surveyed here (5.9 %).…”
Section: Discussionmentioning
confidence: 54%
“…Devices are also being specifically marketed for vaping cannabis [14][15][16] and evidence is emerging of ENDS use to vape recreational drugs [17]. Several studies have shown that ENDS are being used to vape cannabis [18][19][20] with one study finding that vaporisers appealed to marijuana users, who perceive them as having harm-reduction, better taste and more effect from the same amount of marijuana. There are case reports of other drugs being vaped including acetylfentanyl [21,22] and synthetic cannabinoid receptor agonists (SCRA's) [23,24] as well as a news report of students vaping new psychoactive substances (NPS) with 6 users of 'Cloud 9' e-liquid in Detroit reported hospitalised [25].…”
Section: Introductionmentioning
confidence: 99%